Climate change games as tools for education and engagement - Wu, Jason S.; Lee, Joey J. (Nature climate change, 2015)
Whether simple or sophisticated, educational games can help inform the public about climate change, its impacts, and what can be done about it. Scientists, educators and policymakers continue to face challenges when it comes to finding effective strategies to engage the public on climate change. We argue that games on the subject of climate change are well-suited to address these challenges because they can serve as effective tools for education and engagement. Recently, there has been a dramatic increase in the development of such games, many featuring innovative designs that blur traditional boundaries (for example, those that involve social media, alternative reality games, or those that involve direct action upon the real world). Here, we present an overview of the types of climate change game currently available, the benefits and trade-offs of their use, and reasons why they hold such promise for education and engagement regarding climate change.